Sur/Face: Self-Portrait in Porcelain - Nurdian Ichsan (Journal of Visual Art and Design, 2023)
This paper discusses artworks that were created through a practice-led research approach. Considering practice-led research, the content of this paper encompasses every possible relation to the artworks, such as the perspective and statements of practice, considerations, thoughts behind the themes, observations, and interpretations of the creative process. All these aspects are grouped into two sections: the context of the practice and self-reflection on the practice. This research found that material-oriented and media-based approaches are not inseparable in ceramic art practice. Indeed, both perspectives are very valuable to understand the creative process as well as the appreciation of art works. Due to the creative process in art requiring non-linear thinking, the contents of this paper are not hierarchical in one direction. Instead, it can be conceived as offering multiple perspectives to understand the making process and the resulting artifact. In some way, this paper can be considered as a narrative style of writing, which is appropriate to reveal the creative process.